The philosophy and objectives of education in Islam - Khamis, Muhamad Hafiz; Salleh, Mohamad Johdi (2010)
Education is crucial for all mankind. It is gained in order to perfect all aspects of human’s life. To achieve the true education, we must have the knowledge on the philosophy and objectives of education as stipulated in the Al-Quran and Sunnah. These sources help in the effective formulation of producing the complete growth of individual with integrated, balanced, and harmonious personality. The prime task of education is, to the nurture of personal growth. It is through this nurture of the individual and the preservation and transmission of culture that both the individual and society attain a quality of life. A good man is not necessarily a complete man. No one can be regarded as a complete man because there is no end to the growth of human personality. A wide knowledge of many subjects helps in the growth of personality provided a man knows how to adjust to knowledge to behavior, and how knowledge and action are integrated into a broad, total framework of life. Therefore, the aims of this paper is to identify and explain about Islamic education in terms of its concept, education in Islamic perspective, and focus on the philosophy and objectives of Islamic education in the wholly and holy concept of JERISAH as promulgated in the Education Conference in Makkah with some significant examples from the Muslims scholars as aspired in the Al-Quran and Sunnah of the Prophet SAW.